Struktur Kebahasaan Bahasa Indonesia Sebagai Rujukan Penggunaan Bahasa (Morfologi) - Nur Annisa; Rahma Ashari Hamzah; Hasmiati Hasmiati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the linguistic structure of the Indonesian language with a focus on morphology as a reference for proper and effective language use. The research employs a qualitative descriptive method, utilizing literature review and content analysis of various written sources such as textbooks, journals, and scholarly works related to Indonesian morphology. Data are systematically analyzed to identify patterns of word formation, including affixation, reduplication, and compounding in the Indonesian language. The results indicate that affixation is the most dominant and productive morphological process in word formation, followed by reduplication which functions to intensify meaning, and compounding which produces compound words. This study contributes significantly to the development of morphological studies in Indonesian and serves as a valuable reference for language users to gain a deeper understanding of word structures.